INDUSTRI PERTAHANAN INDONESIA DAN PRANCIS - Elisa Jirey Barus; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study discusses the development of the defense industry in Indonesia and France. Self-reliance in producing defense equipment is essential in maintaining a country's security. This can be achieved when the country has a defense industry with the technological capacity and ability to produce all the necessary equipment domestically. However, not all countries are capable of meeting their own needs and must cooperate with more advanced countries to develop their defense industries. The theory used in this study is the typology model of the defense industry. The data used are secondary data derived from books, journals, documents, electronic media, and internet websites. The research method used is qualitative method by analyzing data from the sources mentioned. The results of this study show that France belongs to the Autarky Model typology where it has become one of the top five global exporters, while Indonesia belongs to the Niche-Production Model. Therefore, Indonesia is seeking cooperation partners that can help develop the capacity and technological advancement of defense equipment domestically. France's progress and willingness to share defense technology make defense cooperation with Indonesia possible. Keywords: Defense, Defense Equipment, Defense Industry